1984
DOI: 10.1128/jb.159.3.850-856.1984
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of the nickel-containing hydrogenase of chemolithotrophically grown Rhizobium japonicum

Abstract: The uptake hydrogenase of chemolithotrophically grown Rhizobium japonicum was purified to apparent homogeneity with a final specific activity of 69 ,umol of H2 oxidized per min per mg of protein. The procedure included Triton extraction of broken membranes and DEAE-cellulose and Sephacryl S-200 chromatographies. The purified protein contained two polypeptides separable only by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. They comigrated on native polyacrylamide gels and sucrose density gradients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…In the same experiment, the Oa-dependent hydrogenase activities of bacteroids from the wild-type UPM791 and AL91 strains were 1200 and 870 nmol of Hg oxidized per hour and mg protein, respectively. Since methyiene blue is a primary electron acceptor from the hydrogenase (Harker et al, 1984). these results indicate that the hyp cluster is essential for hydrogenase synthesis in R. leguminosarum bv.…”
Section: Characterization Of T/75 Hup~ Mutantsmentioning
confidence: 68%
“…In the same experiment, the Oa-dependent hydrogenase activities of bacteroids from the wild-type UPM791 and AL91 strains were 1200 and 870 nmol of Hg oxidized per hour and mg protein, respectively. Since methyiene blue is a primary electron acceptor from the hydrogenase (Harker et al, 1984). these results indicate that the hyp cluster is essential for hydrogenase synthesis in R. leguminosarum bv.…”
Section: Characterization Of T/75 Hup~ Mutantsmentioning
confidence: 68%
“…They include Rhodobacter capsulatus [16,45], Rhodocyclus gelatinosus [17], Bradyrhizobium japonicum [18,46], Rhizobium leguminosarum [19,20,47], Azotobacter chroococcum [21], Azotobacter vinelandii [22,48], Wolinella succinogenes [24] and Escherichia coli (isoenzymes 1 and 2, Table 1) ( [23,49,50]; Menon, N.K., Robbins, J., DerVartanian, D.V., Choi, E.C. and Przybyla, A.E., personal communication).…”
Section: He-uptake Membrane-bound Nife-hydrogenasesmentioning
confidence: 99%
“…This nickel-containing hydrogenase (Arp. 1985;Harker et at., 1984;Stults ef ai, 1984) is composed of 33 and 65 kDa subunits encoded by hupS and hupL, respectively (Sayavedra-Soto etat., 1988), Using plasmid-borne tiup-iacZ fusions, it was found that nickel, hydrogen, and oxygen transcriptionaliy r'egulate expression of the operon through a common c/s-acting region 5' of the promoter (Kim and Maier, 1990;Kim etai. 1991).…”
Section: Introductionmentioning
confidence: 99%